Penerapan Fungsi Hukum Pidana Dalam Kasus Investasi Bodong - Adalia Safira Rahma; Riska Andi Fitrionio; Aldi Danuarta; Muhammad Rizka Chamami; Yola Septania Cahyani (Universitas Pendidikan Nasional, 2022)
Law has a function, namely to regulate the life of the people of a country where the law applies. This law provides limits on human behavior so as not to violate the rights and obligations set out in the law. However, of course there will be actions that are not appropriate or against the law that are carried out even though they have been limited by the rules set. This is when criminal law plays a role in tackling crimes that have the potential to threaten stability and legal certainty in society. This study focuses on a recent viral investment fraud case by a well-known figure. Using an empirical case study approach and following the development of cases that are updated from time to time, this study aims to provide a discussion on the implementation of legal functions in cases that occur today. Thus, through this research, it can be seen that the law can play a role according to its function in resolving various criminal cases in Indonesia.